1986
DOI: 10.1038/319246a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sp1 recognizes a DNA sequence in the mouse dihydrofolate reductase promoter

Abstract: Human (HeLa) cells contain a host-cell-encoded transcription factor, Sp1, which is required for transcription of simian virus 40 (SV40) promoters. Since the discovery of Sp1 we have been interested in learning what role this factor plays in uninfected cells. A monkey cellular gene promoter interacts with Sp1, but no gene products linked to this promoter have yet been identified. The finding that the sequence of the 5'-flanking DNA of the mouse dihydrofolate reductase (DHFR) gene contains several regions showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(150 citation statements)
references
References 21 publications
4
146
0
Order By: Relevance
“…The promoter region contains two Sp-1 sites at 757 and +87 at close proximity to CAP sites and another site at position 7508. The Sp-1 sequences have been implicated in transcriptional activation of TATA-less promoters present in housekeeping genes and proto-oncogenes (Dynan et al, 1986). Multiple purine rich GGAA Ets Binding Sites (EBS) were identi®ed (at positions 7653, 7349 and 7278) in the human Fli-1b promoter .…”
Section: Promoter Elementsmentioning
confidence: 99%
“…The promoter region contains two Sp-1 sites at 757 and +87 at close proximity to CAP sites and another site at position 7508. The Sp-1 sequences have been implicated in transcriptional activation of TATA-less promoters present in housekeeping genes and proto-oncogenes (Dynan et al, 1986). Multiple purine rich GGAA Ets Binding Sites (EBS) were identi®ed (at positions 7653, 7349 and 7278) in the human Fli-1b promoter .…”
Section: Promoter Elementsmentioning
confidence: 99%
“…These genes do, however, contain one or more copies of the sequence GGGCGG or its inverse complement CCGCCC upstream from their transcription start point. This sequence is found four times in the mouse DHFR promoter (Dynan et al, 1986) and has been shown to be an important component of the SV40 virus early promoter (BarreraSladana et al, 1985) as well as the thymidine kinase promoter of Herpes simplex virus (McKnight et al, 1984). Examination of the sequence in Fig.…”
Section: (B) Analysis Of the Promoter Regionmentioning
confidence: 99%
“…The 5'-flanking region of exon 1 contained no potential CCAAT and TATA sequences, but contained three potential binding sites for the transcription factor Sp1 (CCGCCC) (Fig. 2A, open box) [9]. A potential binding site for Sp1 was also present at nucleotide position +297 ( Fig.…”
Section: Dna Sequencing and Mapping Of The 5'non-coding Region Of Thementioning
confidence: 99%